2023
DOI: 10.1101/2023.02.24.529842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why Do Hybrids Turn Down Sex?

Abstract: Asexual reproduction is ancestral in prokaryotes; the switch to sexuality in eukaryotes is one of the major transitions in the history of life. The study of the maintenance of sex in eukaryotes has raised considerable interest for decades and is still one of evolutionary biology's most prominent question. The observation that many asexual species are of hybrid origin have led some to propose that asexuality in hybrids results from sexual processes being disturbed because of incompatibilities between the two pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This was suggested by Alberici da as an early stage of the evolution of the Amazon molly and subsequently modeled by Fyon et al (2023). This pathway, however, is not compatible with genomic data showing a single hybrid origin of the Amazon molly (Warren et al, 2018).…”
Section: F 1 Femalesmentioning
confidence: 70%
See 1 more Smart Citation
“…This was suggested by Alberici da as an early stage of the evolution of the Amazon molly and subsequently modeled by Fyon et al (2023). This pathway, however, is not compatible with genomic data showing a single hybrid origin of the Amazon molly (Warren et al, 2018).…”
Section: F 1 Femalesmentioning
confidence: 70%
“…In general, the resulting asexual modes of reproduction are genetically totally (parthenogenesis and gynogenesis) or partially (hybridogenesis) clonal, involve unreduced eggs, and sometimes require sperm to trigger embryogenesis (Avise, 2008;Suomalainen et al, 1987). The evolutionary pathway to emergence of these asexual species is still highly debated: though it is often thought that asexuality appears readily as a direct and immediate result of hybridization (Schlupp, 2005), it has been proposed that asexuality can evolve from sexual hybrids through multiple small and incremental evolutionary steps (Fyon et al, 2023).…”
mentioning
confidence: 99%
“…Rutilus rutilus × Abramis bramma (Slyn'ko, 2000). Fyon et al (2023) suggested that the establishment of a spermdependent parthenogen may be more complex and numerous fundamental traits may evolve gradually. For instance, while the ability to produce unreduced gametes may emerge "instantaneously" as a result of hampered crosstalk between diverged parental genomes (Marta et al, 2023), others, like the ability to reject sperm's genome after fertilization, may evolve subsequently.…”
Section: Indirect Impact On Speciation: Promotion Of Reproductive Iso...mentioning
confidence: 99%
“…Because of their atypical meiosis and non‐Mendelian propagation of genomes, obligate asexuals serve as excellent models for understanding fundamental questions in evolution, ecology, and cell biology (e.g., Bengtsson, 2009; Brockhurst et al, 2014; Dalziel et al, 2020; Laskowski et al, 2019; Lively & Morran, 2014; Meirmans, 2009; Van Valen, 1973). Although seemingly rare compared to sexuals, they evolved independently in different taxonomic groups of metazoans (Fyon et al, 2023), suggesting this trait has high relevance for evolution and represents a fascinating challenge to what we understand as “typical” reproductive mode and sex.…”
Section: Introductionmentioning
confidence: 99%